2022
DOI: 10.3389/fnins.2022.957034
|View full text |Cite
|
Sign up to set email alerts
|

Stretch stress propels glutamine dependency and glycolysis in optic nerve head astrocytes

Abstract: Glaucoma is an optic neuropathy that leads to irreversible blindness, the most common subtype of which is typified by a chronic increase in intraocular pressure that promotes a stretch injury to the optic nerve head. In rodents, the predominant glial cell in this region is the optic nerve head astrocyte that provides axons with metabolic support, likely by releasing lactate produced through astrocytic glycolysis. Our primary hypothesis is that stretching of the optic nerve head astrocytes alters their metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…This may be in response to IOP-induced stress on glia, rather than purely a response to retinal ganglion cell metabolic dysfunction. Supporting this, Pappenhagen et al (84) demonstrated that chronic stretching of ONH astrocytes in vitro (24 h of 12% biaxial stretch at 1 Hz) resulted in a significantly different glycolytic and respiratory activity between control and stretched cells. They observed greater extracellular acidification signifying an increased use of glycolysis, and lower ATP-linked respiration.…”
Section: Glial Metabolic Changes In Glaucomamentioning
confidence: 87%
“…This may be in response to IOP-induced stress on glia, rather than purely a response to retinal ganglion cell metabolic dysfunction. Supporting this, Pappenhagen et al (84) demonstrated that chronic stretching of ONH astrocytes in vitro (24 h of 12% biaxial stretch at 1 Hz) resulted in a significantly different glycolytic and respiratory activity between control and stretched cells. They observed greater extracellular acidification signifying an increased use of glycolysis, and lower ATP-linked respiration.…”
Section: Glial Metabolic Changes In Glaucomamentioning
confidence: 87%